Boiling-driven, wickless, and orientation-independent thermal ground plane. (March 2021) - Moon, Joo Hyun; Fadda, Dani; Shin, Dong Hwan; Kim, Jin Sub; Lee, Jungho; You, Seung M.
Highlights: Wickless, orientation-independent, and flat thermal ground plane (TGP). Thermal ground plane concept with boiling heat transfer instead of evaporative heat transfer. Boiling enhancement with high-temperature conductive microporous coating. Abstract: Dissipating heat from a concentrated heat source presents thermal challenges that often impose limits on the compact packaging of electronic devices. While vapor chambers, heat pipes, pulsating heat pipes, and other devices are available, a new concept of a wickless and flat thermal ground plane (TGP) is presented. Since the new concept does not rely on a wick, and its performance is based on boiling instead of evaporation heat transfer, the limits of the new TGP are related to boiling behaviors. Boiling bubbles, in areas close to the heat source, cause pumping of the fluid in the wickless TGP and promote convection two-phase heat transfer within the entire TGP, especially as the heat flux is increased. Following this new concept, a wickless thermal ground plane (80 mm × 80 mm × 1.6 mm-thick) is fabricated from flat copper sheets and its cavity is filled with degassed liquid water. The performance of the device is tested in dissipating concentrated heat from a 10 mm × 10 mm heat source. Depending on the operating temperature of 40 °C–80 °C, this TGP is experimentally proven to achieve a low thermal resistance of 0.2 K/W or better for a heat flux reaching 1500–2200 kW/m 2 . This performance is due to a copper high-temperature conductive microporous coating (Cu-HTCMC) on the inside of the heating surface. The TGP performs equally well in any orientation, offering an effective thermal conductivity close to twice that of copper. However, its weight is approximately 63% of the weight of a copper block of the same size. The concept and test results, based on the developed TGP, are discussed.